Growth and survival of silver pompano Trachinotus blochii (Lacepede, 1801) at different salinities in inland saline ground water - PATHAK, MADHURI S; LAKRA, WAZIR S; REDDY, APPIDI K; CHADHA, N K; TIWARI, V K; SRIVASTAVA, P P (The Indian Journal of Animal Sciences, 2019)
Inland saline ground water (ISGW) has attracted great interest for commercial aquaculture of marine species in Haryana and Punjab. The silver pompano (Trachinotus blochii), a candidate for mariculture, was investigated for its potential to survive in inland saline water at ICAR-CIFE, Regional Centre, Rohtak, Haryana during 2015–16. The experimental set up comprised ISGW without potassium amendment, ISGW with potassium amendment and artificial sea water of 5 ppt, 10 ppt and 15 ppt salinity. In ISGW without potassium amendment, 100% mortality was observed at 12 h (5 ppt), 24 h (10 ppt) and 48 h (15 ppt). In the second experiment, three treatments (ISW5, ISW10 and ISW15) of ISGW with potassium amendment equivalent to sea water were prepared. A 100% survival was observed at all salinities in ISGW with potassium amendment, similar to the artificial seawater at the end of 90 days. Significantly higher weight gain, specific growth rate (SGR) and average daily growth (ADG) were observed at ISW10 and ISW15 than at ISW5. The plasma osmolality of silver pompano in ISW10 and ISW15 indicated that silver pompano regulates isosmotic condition to maintain the homeostasis of body. The present results indicate that silver pompano can be reared at 10 ppt to 15 ppt salinity with optimum growth and survival in potassium amended ISGW.